2006
DOI: 10.1152/japplphysiol.00424.2004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo monitoring of methemoglobin formation and reduction with broadband diffuse optical spectroscopy

Abstract: We present noninvasive, quantitative in vivo measurements of methemoglobin formation and reduction in a rabbit model using broadband diffuse optical spectroscopy (DOS). Broadband DOS combines multifrequency frequency-domain photon migration (FDPM) with time-independent near infrared (NIR) spectroscopy to quantitatively measure bulk tissue absorption and scattering spectra between 600 nm and 1,000 nm. Tissue concentrations (denoted by brackets) of methemoglobin ([MetHb]), deoxyhemoglobin ([Hb-R]), and oxyhemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
(28 reference statements)
1
48
0
1
Order By: Relevance
“…We assume that in the spectral range (1,000-1,100) nm the absorption is due rather to the main components of the tissue (melanin, water and hemoglobin/ oxihemoglobin); methemoglobin, especially, has the absorption three times greater than oxihemoglobin in this spectral range (Lee et al, 2006), (Fig.13).…”
Section: Optical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that in the spectral range (1,000-1,100) nm the absorption is due rather to the main components of the tissue (melanin, water and hemoglobin/ oxihemoglobin); methemoglobin, especially, has the absorption three times greater than oxihemoglobin in this spectral range (Lee et al, 2006), (Fig.13).…”
Section: Optical Results and Discussionmentioning
confidence: 99%
“…13. The absorption spectra of hemoglobin (Hb-R), Oxihemoglobin (Hb-O 2 ) and Methemoglobin (MetHb) (Lee et al, 2006) In an attempt to change the chromophore to obtain significant rates of MetHb, while seeking to increase photon absorption, J. Moreno Moraga & all (n.d.) started the combined application of microfoam sclerosants, proven to be efficient for vein sclerosis, with the action of pulsed 1.06 µm Nd:YAG laser beams.…”
Section: Optical Results and Discussionmentioning
confidence: 99%
“…Finally, the method reported in the present study is not a serum-based test; thus, it may not exhibit the characteristics of the reliable, fast, low-cost, efficient bedside tests and non-invasive techniques that are clinically required for the assessment of the metHb/(oxyHb+metHb) ratio in cyst fluid. A number of studies have used broadband diffuse optical spectroscopy and frequency-domain near-infrared spectroscopy (NIRS) to assess tissue concentrations of metHb, oxyHb and deoxyHb (32,33). Lee et al (33) reported noninvasive, quantitative in vivo measurements of metHb formation using broadband diffuse optical spectroscopy (33).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used broadband diffuse optical spectroscopy and frequency-domain near-infrared spectroscopy (NIRS) to assess tissue concentrations of metHb, oxyHb and deoxyHb (32,33). Lee et al (33) reported noninvasive, quantitative in vivo measurements of metHb formation using broadband diffuse optical spectroscopy (33). NIRS may provide new avenues for future determination of the metHb/(oxyHb+metHb) ratio through transvaginal application of this modality.…”
Section: Discussionmentioning
confidence: 99%
“…The probe was placed on the shaved surface of the right inner thigh of the animal for muscle measurements. The broadband DOS system combines multi-frequency domain photon migration with timeindependent near-infrared spectroscopy to accurately measure bulk tissue absorption and scattering spectra [26][27][28][29][30][31][32]. Tissue concentrations of oxy-and deoxyhemoglobin, water, and CytcOx redox state changes (changes from baseline of the differential between oxidized and reduced CytcOx concentrations) were calculated by a linear least squares fit of the wavelength-dependent extinction coefficient spectra of each chromophore as previously reported.…”
Section: Diffuse Optical Spectroscopymentioning
confidence: 99%